The Impact of Using ChatGPT: Students’ Perspectives in an Indonesian Private University - Yuli Ari Sandy; Paulus Kuswandono (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
This This study examined the impact of using ChatGPT on five postgraduate English education students at a private university in Yogyakarta, both the benefits and challenges. A qualitative approach was used in this research with open-ended questionnaires and semi-structured interviews to gather the data. The researcher applied NVivo and triangulation to analyze the data. This method allows the researcher to understand the perspectives of Indonesian higher education students when using ChatGPT. There are three specific challenges identified: 1) difficulty in creating appropriate prompts, 2) doubts about its validity and reliability, and 3) concerns about privacy and ethical issues. The benefits of using ChatGPT in their academic assignments are: 1) increasing creativity and critical thinking skills, and 2) enhancing collaborative learning. To mitigate these issues, this study highlights the significance of digital literacy in using ChatGPT ethically and effectively. These findings suggest that Indonesian higher education institutions should provide adequate training and establish balanced ethical guidelines. Addressing these challenges can create a more supportive learning environment and improve student outcomes and future career opportunities.